An investigation into challenges faced by full time teaching heads in primary schools in Shurugwi district - Ganda, Admore (Midlands State University, 2020)
The study sought to establish the challenges that are faced by full time teaching heads in primary schools in Shurugwi district with a view to suggest strategies that can be used to solve these challenges. Literature review indicated that heads are faced with challenges that include dual roles and time management. It also suggested that these can be solved through delegation of duties and having non teaching heads in all schools. The research was qualitative in nature so it adopted a descriptive survey. 25 primary schools were targeted. From these schools a sample size of 20% (5 school heads and 20 students) was drawn. The targeted participants were heads of schools and their classes. The schools to be involved in the study were purposively sampled for easy accessibility since schools with full time teaching heads are scattered around the whole district while learners were chosen using simple random selection. The researcher used questionnaires and interviews to collect data. The researcher administered the questionnaires and interviewed the learners. Appointments were made through telephone calls with the heads of schools. The research findings concluded that fulltime teaching heads are faced with challenges which include dual roles, time management and workload. These challenges are a result of the dual roles performed by the head. As a result these heads are failing to perform effectively and efficiently in both roles. It was also noted that learners are affected by being left unattended most of the time and this later impacts on their performance academically. Basing on these conclusions from the findings it was recommended that all schools regardless of their sizes should have non teaching heads, heads to delegate some of their duties to other staff members and heads to work extra hours in order to balance the carrying out of the dual roles.